Pliocene volcanic terrain of the South Caucasus as a missing link in Eurasian palaeobiogeography: Dating and palaeoenvironments of vertebrate assemblages of the Jradzor locality, Armenia - Lazarev, Sergei; Maul, Lutz Christian; Kuiper, Klaudia; Becker, Damien; Bukhsianidze, Maia; Hovakimyan, Hayk; Sahakyan, Lilit; Vasilyan, Davit (Palaeogeography, palaeoclimatology, palaeoecology, 2023)
Cenozoic faunal exchanges between Europe, Asia, Africa and America played a key role in shaping modern-day Eurasian ecosystems with dispersal pathways controlled by the dynamics of natural palaeogeographic barriers (e.g., deserts, isthmuses, large water bodies, etc.). The South Caucasus is a mountainous region between Asia and Europe, which served as an important dispersal route during the late Cenozoic for the intercontinental exchanges of diverse terrestrial vertebrates. The Pliocene geology of this region is dominated by volcanic and volcaniclastic deposits that are generally not favourable for fossil preservation. However, a few rich fossil vertebrate faunas do occur although they lack comprehensive palaeoenvironmental and age constraints. In this paper, we present an integrated study of the stratigraphy and palaeontology of the Jradzor section located in the Gegham volcanic province of Armenia, to improve knowledge of late Cenozoic dispersal pathways. The 57-m-thick succession comprises 19 fossiliferous horizons with at least 48 identified vertebrate taxa (excluding birds). The palaeoenvironmental reconstruction suggests that the succession was deposited within a short-lived dammed lake that was subject to pyroclastic density flows, and later evolved into soil catenas. Taphonomic observations indicate that pyroclastic flows caused a high mortality of small-size vertebrates in most fossiliferous horizons, while a catastrophic lahar buried the large vertebrate fauna. Multiproxy dating places the studied section between 4.3 and ∼ 3.03 Ma and the mammalian fauna correlates to the MN15. Comparison with similar age localities from across the region shows that Jradzor comprises the most continuous Pliocene succession with the highest number of fossil taxa and fills the MN15 interregional gap. The rich fossil vertebrate faunas have Asian and primarily European affinities. Findings show that the South Caucasus was a significant dispersal route for terrestrial vertebrates between Europe, Asia and Africa, and is of crucial importance for understanding Eurasian palaeogeography. •A new vertebrate fauna with >49 taxa from the Pliocene volcanic terrain of the South Caucasus.•The Jradzor fossil record dated between 4.3 and 3.1 Ma fills the MN15 interregional gap.•High mortality on site was mainly caused by pyroclastic density currents and lahars.•MN15 zone of the South Caucasus mammalian record has Asian and predominantly European affinities.•The South Caucasus is a key palaeobiogeographic tying point between Europe, Asia and Africa.